Proses Netralisasi pH pada Air Gambut di Desa Sawahan Kecamatan Cerbon Kabupaten Barito Kuala - Sulaiman Hamzani; Munawar Raharja; Zulfikar Ali As (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: The Neutralization Process of pH on Peat Water in Desa Sawahan Kecamatan Cerbon Kabupaten Barito Kuala. Desa Sawahan, Kecamatan Cerbon, Kabupaten Barito Kuala, located in the area of peatlands with a pH of water, based on laboratory results, is 3.0. This condition is classified as extreme acid, because pH less than 3.5. Neutralization of the peat water aimed to change the pH or acidity of the water to be normal (pH 7-8) and could help the next process. To raise the pH of acidic water, quicklime (CaO) or limestone (CaCO3) was very appropriate, because they were cheap and easy to be applied. This study is experimental, the laboratory-scale trials with variations: the concentration of solubility of lime and jartest, to obtain the optimum dose of coagulant for improving the quality of pH. Results of the experiments on the variation of the solubility of limestone with varying concentrations showed relatively similar results, ie at a concentration of 1.0%, the pH of the water became 12.49; at a concentration of 0.5%, the pH of the water became 12.47, and at a concentration of 0.1%, the pH of the water became 12.18. In the next test, the addition of lime solution with a concentration of 0.5% as much as 9 mL in 500 mL peat water sample were able to raise the pH from 4.06 to 7.77. Jar test results showed that the injection of 5 mL solution of lime and alum 2 mL were able to raise the pH of peat water from 4.02 to be 7.24 so as to meet the requirements of drinking water with pH 6.5-8.5. To neutralize the peat water with a pH of 4 is required optimum dose of lime solution with a concentration of 0.5% as much as 5 mL (50 mg/L) and alum solution with a concentration of 0.5% as much as 2 mL (20 mg/L). Keywords: Neutralization of pH; peat water; jartest.